GE_GERICHTE C/26383/2013 vom 24. März 2017 - GE Cour de justice (2017)
SUSPENSION DE LA PROCÉDURE ; OPPORTUNITÉ ; PRINCIPE DE LA CÉLÉRITÉ ; QUESTION PRÉJUDICIELLE ; SOLIDARITÉ PASSIVE | CPC.126; Cst.29.1; CPC.124.1; CO.143; CO.144.1;